Unraveling the Seasonality of UV Exposure in Reef Waters of a Rapidly Warming (Sub-)tropical Sea - Overmans, Sebastian; Agustí, Susana (Frontiers in Marine Science, 2020)
Ultraviolet radiation (UV) is a crucial abiotic stressor that can have severe impacts on biota residing in the upper euphotic zone, especially if UV stress coincides with other stressors such as extreme sea surface temperatures (SSTs). Exposure-dependent effects of UV exposure have been described for a broad range of marine taxa and ecosystems such as coral reefs, yet little is known about the magnitude and seasonality of UV exposure in natural waters. In the present study, we determined how daily exposure of UV-B and UV-A varies seasonally along the water column of a reef system in the central Red Sea, and identified periods when damaging UV levels are likely to coincide with episodes of extreme SST, both presently and in the future. Between July 2016 and September 2018, UV spectroradiometer profiles were recorded fortnightly at a pelagic site adjacent to a mid-shore reef off the Saudi Arabian Red Sea coast, while atmospheric UV-B and UV-A irradiances were measured in 10-minute intervals. Additionally, we quantified the concentration of chlorophyll-a (Chl-a) and absorption by chromophoric dissolved organic matter (aCDOM) in the reef as well as the surrounding waters. Biologically effective optical depths (Z10%) ranged from 6.3–12.9 m (UV-B) and 14.4–27.3 m (UV-A), with the highest UV transparency being observed in late summer when photodegradation of dissolved organic matter (DOM) was most intense and the concentration and molecular weight of CDOM were at their lowest. Incident UV peaked a few weeks prior to this later summer maximum in UV transparency. Consequently, organisms living close to the water surface experienced their most intense UV exposure in May/June, while the timing of maximum UV exposure for biota below ~ 2–4 m coincided with the annual peak in water transparency and water temperature, i.e., in July/August. However, SSTs in the Red Sea are increasing at a rapid rate due to climate change, with the consequence that extreme temperatures are occurring earlier in the year and may eventually coincide with extreme UV radiation in shallower areas of the reef. This development could have potentially detrimental effects on highly sensitive, immotile reef biota such as reef-building corals.